An Epidemiological Study of Traffic Accidents Leading to Pedestrians' Death in Ahwaz, Iran in 2015-2017 - Tayebeh Rakhshani; Zahra Motlagh; Poran Hezarvand Zanganeh; Davood Farsi; Banafsheh Bizhani; Seyyed Saeed Hashemi Nazari (Shiraz University of Medical Sciences, 2022)
Background: Traffic accidents are considered a major public health problem in many parts of the world. This study aimed to investigate the epidemiology of the accidents leading to pedestrians' death in Ahvaz, Iran, in 2015-2017.Methods: This descriptive cross-sectional study was conducted in 2015-2017. The statistical population was pedestrians who died in traffic accidents in Ahvaz city. The data collection source was the Forensic Medicine Organization. The data were analyzed using the SPSS 16 software using descriptive statistics and chisquare test. Results: Among the 165 pedestrians who died in traffic accidents, 72.1% (119 people) were male and 27.9% (46) female. The mean age of the deceased subjects was 38.38±2.44. The highest frequencies of death in the age groups over 65, under 7, and 25-34 years old were 19.4% (32 people), 14.5% (24 people), and 14.5% (24 people), respectively. Most of the deceased were illiterate (34.5% (57 people)), self-employed (24.2% (40 people)). The final cause of death in more than half of the pedestrians was head trauma (64.8%) (107 people), and most of the deceased had died in hospitals (71.5%) (118 people).Conclusion: Considering that young and older people are two high-risk groups in car accidents, training safety and improving pedestrian safety by creating a safer environment can play a significant role in reducing deaths.